Geologists, FIFO work practices and job satisfaction. (1st October 2016) - Barclay, M. A.; Harris, J.; Everingham, J.-A.; Kirsch, P.; Shi, M.
Abstract : This paper presents the findings of a study into the factors linked to the job satisfaction and well-being of fly-in fly-out (FIFO) workers in the Australian resources sector, focusing on geologists. The findings indicate that geologists have high levels of job satisfaction and most appear to have adapted successfully to the demands of the FIFO lifestyle. While a number of studies have raised a range of concerns about the impact of FIFO work arrangements on the health and well-being of FIFO workers, this study provides a more granular examination of factors that may contribute to a greater understanding of the link between job satisfaction and physical and mental health. The main finding from the study was that job satisfaction was high among these early career professionals who are motivated by intrinsic career rewards and who have limited domestic responsibilities. The second major finding was that, although respondents reported good physical and psychological health, a small number were experiencing serious psychological distress.